1992
DOI: 10.1246/cl.1992.2145
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Perovskite-type LaFeO3 by Thermal Decomposition of Heteronuclear Complex, {La[Fe(CN)6]·5H2O}x

Abstract: Submicron perovskite-type, LaFeO3, powders were prepared by the thermal decomposition of a title cyanide-bridged heteronuclear complex. The decomposition begins at about 50 °C and the formation of LaFeO3 proceeds above 580 °C. Mean particle diameter and specific surface area were 50 nm and 22.7 m2/g, respectively, for the LaFeO3 obtained by calcining at 620 °C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…ABO 3-δ perovskite type oxides (0 £ δ £ 0.5, A= Lanthanide or alkaline earth, B= transition metal) have a great technological interest due to their electrical, magnetic and catalytic properties. They have been extensively used as catalyst in redox reactions, as in the reduction of nitrogen oxides and SO 2 , hydrogenation of hydrocarbons and in the elimination of atmospheric pollution. In the specific case of A=lanthanum, its oxides are particular suitable for applications as a material for sensors, for the detection of vapors and gases such as humidity, alcohol, oxygen, hydrocarbons, CO and NO 2 3-5 .…”
Section: Introductionmentioning
confidence: 99%
“…ABO 3-δ perovskite type oxides (0 £ δ £ 0.5, A= Lanthanide or alkaline earth, B= transition metal) have a great technological interest due to their electrical, magnetic and catalytic properties. They have been extensively used as catalyst in redox reactions, as in the reduction of nitrogen oxides and SO 2 , hydrogenation of hydrocarbons and in the elimination of atmospheric pollution. In the specific case of A=lanthanum, its oxides are particular suitable for applications as a material for sensors, for the detection of vapors and gases such as humidity, alcohol, oxygen, hydrocarbons, CO and NO 2 3-5 .…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis using chemical processing methods is performed at considerably lower temperatures than that by the solid-state reaction methods, and finer polymetallic-type products are obtainable [11]. We have been investigating the preparation of a wide range of perovskite-type oxides by the thermal decomposition of the appropriate heteronuclear complexes [12][13][14][15][16]. It is well known that a number of perovskite-type oxides prepared in air display p-type semiconducting properties, and their conductivity increases with the adsorption of oxidizing gases, such as O 2 and NO 2 [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…From this viewpoint, we have investigated the thermal decomposition behavior of cyanide-bridged 3d-4f heteronuclear coordination polymers, Ln[M(CN) 6 ] Á 5H 2 O (Ln = lanthanide(III), M = Fe(III) or Co(III)), and shown that these coordination polymers are excellent precursors of perovskite-type oxides, LnMO 3 [1][2][3]. Nevertheless, there has been an inevitable problem: these coordination polymers are poorly soluble in water and almost insoluble in usual organic solvents, since an extremely sturdy three-dimensional infinite network structure is constructed by the 3d-CN-4f linkages, and hence thermal decomposition process via such solid precursors is the only method for the design of functional materials consisting of perovskite-type oxides.…”
mentioning
confidence: 99%
“…The coordination polymer, La[Fe(CN) 6 ] Á 5H 2 O, was synthesized, in the usual way, by mixing the equimolar amounts of La(NO 3 ) 3 Á 6H 2 O and K 3 [Fe(CN) 6 ] in water [1]. Amounts (g) of La[Fe(CN) 6 ] Á 5H 2 O soluble in the mixed solvent (1 ml) of EG and water with various volume ratios were determined at ambient temperature ( Fig.…”
mentioning
confidence: 99%